Effects of Giving Iodized Salt, Counseling of Iodine and Goitrogenic Sources of Food in Mothers Who Have Elementary School Children Against Urinary Iodine Excretion - I Ketut Swiryajaya; Iswari Pauzi (Health Notions, 2019)
As a result of IDD is the occurrence of impaired child growth makes researchers interested in conducting research on "Provision of iodized salt, food counseling about the source of iodine and goitrogenic substances with urinary iodine excretion status in elementary school children". Research on IDD is often carried out in primary school-age children, aged 6-12 years because of their vulnerability to iodine deficiency. The purpose of this study was to determine the effect of iodized salt interventions and counseling patterns of iodized and goitrogenic food consumption patterns on levels of urinary yodiun excretion in families with elementary school children. Research methods: The design of this study included quasi-experimental using a specific design that is "pre and post test control group design". The study population was elementary school children with a sample size of 30 children aged 9 -12 years in each group. Data collected included the consumption of nutrients by the 24-hour recall method, the results of urine iodine examination by the spectrophotometric method. The collected data is then analyzed with an independent sample T test. The results showed there were differences in urinary yodiun excretion levels in the two groups (treatment and control), while the mean in the treatment group before intervention was 106.97 ug / L and after the intervention was 43.19 ug / L. Whereas in the control group, the level of urinary yodiun excretion before intervention was 117.30 μg / L and after the intervention was 243.19 μg / L. The mean of respondents who consumed goitrogenic sources in the treatment group before the intervention (Yes = 63%, No = 37%), after the intervention (Yes = 23%, No = 77%). Whereas in the Control group before the intervention (Yes = 56%, No = 73%), after the intervention (Yes = 23%, No = 77%). The average amount of protein consumption before treatment was 47.91 µg/L ± 6.54 and 50.15 µg/L ± 12.52 after treatment. For consumption, an increase with a mean before treatment was 89.88 µg/L ± 38.45 and after treatment was 113 µg/L ± 26. The results of the independent sample t-test showed that in the treatment group there was no significant difference between after and before the intervention (p = 0.058). Whereas in the control group there were significant differences between before and after the intervention (p = 0.002). It can be concluded that there are many factors that need to be controlled in the provision of interventions, especially the use, type of salt and goitronic as well as the method of examination of iodine analysis in urine. Keywords: iodized salt; iodine food sources; goitrogenic; urinary iodine excretion